Extruded Aluminum Shines in Multifamily and Commercial Building Projects. - Fredrickson, Erika (Architectural Record, 2021)
Extruded aluminum is unlike many other building materials because it does not need to fit standard profiles. Aluminum can be extracted from the bauxite and then smelted to form the aluminum metal that most people know.